The political instrumentality of cultural memory - Corcoran, Farrel (Javnost (Ljubljana), 2002)
This paper examines how cultural memory relates to political communication, especially in polities where the stability of political structures cannot be assumed. It argues that the dominant thrust of political communication research is to emphasise the synchronic dimension in political culture at the expense of the diachronic. This makes it more difficult to discern the role played by political actors who can achieve control over the shaping and parsing of the reservoir of stored meaning that is embedded in cultural memory. The diachronic dimension in political communication can be examined most clearly at those "sites of memory" where the slow formation of ideology, consensus and collective identity takes place. These reflections on the relationship between time, memory and the exercise of political power are worked out in a case study of contemporary Ireland, where moves in the late 1990s to end the conflict in Northern Ireland have yielded political structures that are still quite unstable, where the past surges into the present in scenarios quite unlike what is often described as the flattening oftime and memory assumed to be at the heart of late modernity.
Keywords: communication; komuniciranje; politične komunikacije; identiteta; kulturna identiteta; Severna Irska